The Reflection Of Urban Madura Society In Apolongtret's Work - Pitono, Punjul (Sekolah Tinggi Kesenian Wilwatikta Surabaya, 2024)
The Madurese community in Surabaya is the source of inspiration for Apolong's artwork. The social structures in their hometown are still firmly upheld even if they have moved to Surabaya. Many Madurese settlements, notably those in Sawah Pulo and Semampir Surabaya, have arisen as a result. The purpose of this effort is to shed light on Surabaya's cultural variety. However, it also makes an effort to understand Madura within the framework of its metropolitan existence. It is hoped that people will be conscious of the need to appreciate, comprehend, and understand other ethnic groups.